Modelling and analysis of real-time and reliability for WSN-based CPS. Issue 2 (9th May 2019) - Zhang, Junhua; Zhu, Yi; Xiao, Fangxiong
WSN-based CPS can be used to collect information from remote environment and control it. Delay and dependability directly affect the running quality of WSN-based CPS. In this paper, we present a specified process calculus to model the running of the system, including its real-time and reliability character. Then we design a group of algorithms to calculate the reliability of the system under certain responsible time constraint. Using these methods, we can formally depict the running of WSN-based CPS, and can assess real-time and reliability of WSN-based CPS quantitatively. We illustrate our ideas through bank night automatic monitoring and emergency system, and we can improve the system's reliability from 0.58 to 0.87 and higher gradually.